A fNIRS Investigation of Speech Planning and Execution in Adults Who Stutter. (15th May 2019) - Jackson, Eric S.; Wijeakumar, Sobana; Beal, Deryk S.; Brown, Bryan; Zebrowski, Patricia; Spencer, John P.
Abstract: Our study aimed to determine the neural correlates of speech planning and execution in adults who stutter (AWS). Fifteen AWS and 15 controls (CON) completed two tasks that either manipulated speech planning or execution processing loads. Functional near-infrared spectroscopy (fNIRS) was used to measure changes in blood flow concentrations during each task, thus providing an indirect measure of neural activity. An image-based reconstruction technique was used to analyze the results and facilitate their interpretation in the context of previous functional neuroimaging studies of AWS that used positron emission tomography (PET) or functional magnetic resonance imaging (fMRI). For planning, we compared neural activity associated with high versus low planning load in AWS and CON. For execution, we compared the neural activity associated with overt versus covert naming in AWS and CON. Broadly, group level effects corroborate previous PET/fMRI findings including under-activation in left-hemisphere perisylvian speech-language networks and over-activation in right-hemisphere homologs. Increased planning load revealed atypical left-hemisphere activation in AWS, whereas increased execution load yielded atypical right fronto-temporo-parietal and bilateral motor activation in AWS. Our results add to the limited literature differentiating speech planning versus execution processes in AWS. Highlights: This report includes the largest sample of AWS to undergo fNIRS to date. AWS showed atypical activation in left speech-language regions for planning and right hemisphere homologs for execution. Atypical right hemisphere activation comprises a known inhibitory network Group main effects were generally in line with previous PET/fMRI studies of AWS.